2018
DOI: 10.2147/cmar.s174623
|View full text |Cite
|
Sign up to set email alerts
|

EGFR-TKI-sensitive mutations in lung carcinomas: are they related to clinical features and CT findings?

Abstract: BackgroundEpidermal growth factor receptor (EGFR) mutation testing is restricted to several limitations. In this study, we examined the relationship between EGFR mutation status and clinicoradiological characteristics in a Chinese cohort of patients.Materials and methodsThe data of patients who were diagnosed with lung carcinoma and underwent both EGFR testing and chest computed tomography (CT) at our hospital between January 1, 2011, and November 31, 2015, were retrospectively analyzed. The age, sex, and smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…A total of 34 retrospective diagnostic accuracy studies were included in the final analysis [9] , [12] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] . These articles assessed 10355 individuals; the sample size fluctuated between 64 and 864 patients per study.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 34 retrospective diagnostic accuracy studies were included in the final analysis [9] , [12] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] . These articles assessed 10355 individuals; the sample size fluctuated between 64 and 864 patients per study.…”
Section: Resultsmentioning
confidence: 99%
“…Our system showed that a higher proportion of GGO was linked with mutations in EGFR , consistent with most previous study findings. 8,9,22 However, some previous studies have reported that either no significant correlation was observed between mutations in EGFR and GGO 23 or mutations in EGFR were more common in lesions with >50% solid component. 24,25 The difference could be a result of insufficient recruitment of early-stage patients, or because different definitions were used for the quantification and classification of GGO.…”
Section: Discussionmentioning
confidence: 98%
“…Molecular targeted therapy has been proved to effectively prolong progression-free survival of patients with lung adenocarcinoma (13,14). Recent studies have attempted to associate clinical, radiological features with EGFR mutations of lung adenocarcinomas with aim to determine predictors for effective EGFR status in a non-invasive way (15)(16)(17). In our study, we found that smoking history, tumor size and air-containing space were signi cant independent factors relevant to EGFR mutations in patients with early-stage lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%